How Are Non-Performing Loans Influencing the Banks’ Efficiency? - Diakomihalis, Mihail; Economakou, Sofia (International Finance and Banking, 2024)
Non-Performing Loans portfolio (NPLs) is a major issue faced by the financial system worldwide and in Greece as well with extremely influence during the financial crisis decade. The purpose of this research is to investigate and determine if and how the NPLs influence the efficiency indicators of the Greek banks and specifically how they affect efficiency of the banks. The empirical investigation of Non-Performing loans included a comparative study of indicators of efficiency of the Greek banks, National Bank of Greece, Piraeus Bank, Alpha Bank, Eurobank, Attica Bank and the Co-operative Banks of Epirus, Crete, Thessaly, and Serres, for the year 2017. The conclusions resulted concern the display of financial size of the bank sample, the correlation of loans with outflows, the multifaceted analysis of linear regression to control the effects of loans and finally the effect of lending on the banks’ performance.